Run off Plot Studies with Different Grasses with Special Reference to Conditions Prevailing in the Himalayas and the Siwalik Region - Gupta, Raghunath S.; Khybri, Motilal; Singh, Bhagwan (Indian Forester, 1963)
Experiments on Run-Off Plots with different grasses were originally started as a part of the activities of the Soil Conservation Branch of the Forest Research Institute, Dehra Dun. Later on, the S.C. Branch was transferred to the Soil Conservation Board on its formation. The object of these experiments was to find the suitability of different grasses for erosion control and incidentally for their use in connection with grazing problems in forestry. The different grasses tried were Cynodon dactylon (dub grass), Brachiaria mutica (para grass), Cynodon plaectostachyus (giant star grass), Eulaliopsis binata (bhabar grass), and Panicum antidotale (blue panic grass). Controls consisted of plots with natural grasses, bare plot, and bare and ploughed plot. The effectiveness of grasses in erosion control could be judged from the fact that the ’bare’ and the ’bare and ploughed’ plots had 3-4 times the total run-off and 600 to 4,000 times the soil-loss as compared to the grass covered plots in certain storms. Damage by splash due to rain drops was also measured by suitable devices. Cyanodon dactylon (dub grass) could be recommended as very suitable grass on account of many advantages accruing from it. It was also found that erosion could be serious not only during rains but also in the winter season where winter rains are excessive. An instance is quoted where bare plots had nearly 9 times the ’run-off’ and 400 to 800 times the ’soil loss’ as compared with the grass covered plot in a winter storm. Frost preceding winter rain, and freezing of soil with its consequent bulging and loosening help soil-erosion in bare plots. Mesh of grass roots, where present in the sub-soil, effectively controls all these erosive factors. Winter erosion is of special importance in the Himalayas and the Siwalik region because of heavy and severe winter showers and severe frost which frequently occur.